A novel analog-to-residue conversion scheme based on clock overlapping technique - Huang, Qi (2013)
Residue Number System (RNS) offers significant advantages over conventional number system in terms of parallel signal processing and power consumption. This makes it ideally suitable for communication, computer security, digital signal processing, in which long word addition and multiplication are involved critically. However, traditional Analog-Digital (binary)-Residue conversion scheme requires large silicon area and high power consumption. Therefore, direct Analog-to-Residue conversion starts to attract due attention from circuit designers and researchers. This paper describes a new approach to the direct conversion based on clock overlapping technique and the hardware complexity grows only logarithmically with the bit-resolution.